Effect of graphite on poling time and electrical properties of barium zirconate titanate-Portland cement composites - Supakporn Aodkeng (2018)
© 2018 Taylor & Francis Group, LLC. The 0–3 connectivity piezoelectric ceramic-cement composites of barium zirconate titanate (BaZr0.05Ti0.95O3, BZT) and Portland cement were developed for smart concrete structure applications. In this study, graphite powder was added at 0–2.0% by volume into the composites in order to improve the poling process of 0–3 connectivity cement-based piezoelectric composites. Microstructure, dielectric properties (Ɛr), piezoelectric coefficient (d33), and conductivity were studied. The results indicated that the highest piezoelectric coefficient of 30.76 pC/N was found at 0.5% by volume of graphite content. Moreover, total poling time was reduced when graphite was added.